Braquiópodes da Classe Strophomenata como Indicadores Paleoambientais no Devoniano da Bacia do Paraná - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
The Strophomenata are Rhynchonelliformea brachiopods characterized by having shells with strophic hinge, essentially plano-convex or concave-convex, pseudopontuate, the latter being an important feature in distinguishing them from other brachiopods. The Class Strophomenata includes four major orders, Strophomenida, Productida, Orthotetida and Billingsellida that together contain more than one third of all described Paleozoic genera of articulated brachiopods. Thus, the main objective of this work was to elucidate how the representatives of the class Strophomenata are distributed in the Devonian deposits of the Ponta Grossa Formation in the Paraná Basin. Highlighting their taxonomy, ecological attributes, stratigraphic position and stratigraphic distribution in the regional sequence framework. For this purpose, 660 samples collected during the Technical Project of Paleontological Salvage containing the biological group of interest were processed. The laboratory work involved curation, ensuring its integrity, documentation, protection and conservation, as well as accurate taxonomic identification, carried out according to the rules of zoological nomenclature and based on quantitative parameters, the description of the sedimentary and taphonomic features present in the samples was also carried out. Through the taxonomic analysis, seven species were identified: Australostrophia mesembria, Babinia parvula, Kentronetes? iclaense, Sanjuanetes sp., Pleurochonetes falklandicus, Pleurochonetes sucuroi? and Schellwienella sp. Being the first record of Sanjuanetes sp. in the eastern edge of the Paraná Basin. Taphonomic analyses revealed six modes of occurrence for Strophomenata from the Ponta Grossa Formation that can be associated with three distinct taphofacies characterizing environments ranging from the lower shoreface to the offshore. The paleobathymetric distribution of the identified specimens showed that the Strophomenata present in the Devonian of the Paraná Basin can be considered an adequate tool to infer the paleobathymetric of the fossil record. They also areassociated with transgressive cycles.
Keywords: Rhynchonelliformea; Formação Ponta Grossa; Tafonomia; Paleobatimetria; Devoniano; Rhynchonelliformea; Ponta Grossa Formation; Taphonomy; Paleobathymetric; Devonian; CNPQ::CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS